2006
DOI: 10.1590/s1677-04202006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Endo-beta-mannanase from the endosperm of seeds of Sesbania virgata (Cav.) Pers. (Leguminosae): purification, characterisation and its dual role in germination and early seedling growth

Abstract: Abbreviations: ABA, abscisic acid; BSA, bovine serum albumin; CAP, micropylar area around the radicle emergence point or endosperm cap; DAB, diaminobenzidine; DEAE, diethylaminoethyl; IgG, immunoglobulin G; LAT, lateral coat plus endosperm; LBG, locust bean gum; η sp , specific viscosity; PBS, phosphate buffer saline; pI, isoelectric point; RAD, radicle tip; SDS-PAGE, sodium dodecyl sulfate polyacrylamide gel electrophoresis; Visc. U., viscometric units.Galactomannans are storage cell wall polysaccharides pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
(44 reference statements)
1
8
0
2
Order By: Relevance
“…Lisboa et al (2006) observed that the molecular weight of a-galactosidase is about 45 kDa, which corroborates the hypothesis that the 44 kDa protein may be one of the active isoforms of the enzyme. Feurtado et al (2001) suggested the presence of at least three isoforms of a-galactosidase during and after germination of tomato seeds, demonstrating high homology of the active form (40 kDa) with others galactosidases, especially with the a-galactosidase of the coffee seeds (Zhu and Goldstein 1994).…”
Section: Galactomannan Mobilisationsupporting
confidence: 84%
“…Lisboa et al (2006) observed that the molecular weight of a-galactosidase is about 45 kDa, which corroborates the hypothesis that the 44 kDa protein may be one of the active isoforms of the enzyme. Feurtado et al (2001) suggested the presence of at least three isoforms of a-galactosidase during and after germination of tomato seeds, demonstrating high homology of the active form (40 kDa) with others galactosidases, especially with the a-galactosidase of the coffee seeds (Zhu and Goldstein 1994).…”
Section: Galactomannan Mobilisationsupporting
confidence: 84%
“…The membranes were incubated overnight in a solution containing anti-endo-β-mannanase antibody diluted 1:200 in PBS, prepared in rabbits against endo-β-mannanase purified from coffee seeds, gently provided by Prof. Dr. J. Giorgini from the Department of Biology of University of São Paulo, Brazil. Specificity of the antibody to S. virgata endo-β-mannanase was shown by Lisboa et al (2006) and Tonini et al (2006). The membranes were washed with 50 mM Tris-HCl pH 7.4 and subsequently incubated for 1 h in a solution containing goat anti-rabbit IgG conjugated to peroxidase diluted 1:200 in PBS.…”
Section: Tissue Printingmentioning
confidence: 99%
“…The purified endo-β-mannanase, obtained as described by Lisboa et al (2006), after separation by SDS-PAGE (Laemmli 1970, Hames 1990, was transferred to a nitrocelulose membrane, for 2 h in 0.4 M glycine-20% methanol buffer using a constant current of 400 mA, which was subsequently incubated for 1 h in 100 mM potassium ferricyanide, to inhibit peroxidase seed activity (Guéra and Sabater 2002). The membrane was blocked for 3 h in a solution containing 0.1% gelatine, 1% BSA in 0.1 M phosphate buffer saline (PBS) pH 7.0, with some drops of Tween 20.…”
Section: Western Immunoblottingmentioning
confidence: 99%
“…According to Lisboa et al (2006), the action of the α-galactosidase from S. virgata on galactomannan is a necessary condition to grant access of endo-β-mannanase to the main chain of galactomannan polymer in seeds of S. virgata. This explains the appearance of α-galactosidase activity prior to endo-β-mannanase ( Fig.…”
Section: Galactomannan Hydrolases Activities and Localisation Of Endomentioning
confidence: 99%